Bioenergy potential of Wolffia arrhiza appraised through pyrolysis, kinetics, thermodynamics parameters and TG-FTIR-MS study of the evolved gases. (April 2018) - Ahmad, Muhammad Sajjad; Mehmood, Muhammad Aamer; Liu, Chen-Guang; Tawab, Abdul; Bai, Feng-Wu; Sakdaronnarong, Chularat; Xu, Jianren; Rahimuddin, Sawsan Abdulaziz; Gull, Munazza
Graphical abstract: Highlights: Waste biomass of Wolffia arrhiza is abundant and freely available. It was subjected to pyrolysis followed by TG-FTIR-MS analyses. Kinetics and thermodynamic parameters of its pyrolysis were elucidated at three heating rates. The biomass showed considerable potential for bioenergy and chemicals production. Abstract: This study evaluated the bioenergy potential of Wolffia arrhiza via pyrolysis. The biomass was collected from the pond receiving city wastewater. Oven dried powdered biomass was exposed to thermal degradation at three heating rates (10, 30 and 50° C min −1 ) using Thermogravimetry–Differential Scanning Calorimetry analyzer in an inert environment. Data obtained were subjected to the isoconversional models of Kissenger-Akahira-Sunose (KSA) and Flynn–Wall–Ozawa (FWO) to elucidate the reaction chemistry. Kinetic parameters including, Ea (136–172 kJmol −1 ) and Gibb's free energy (171 kJmol −1 ) showed the remarkable bioenergy potential of the biomass. The average enthalpies indicated that the product formation is favored during pyrolysis. Advanced coupled TG-FTIR-MS analyses showed the evolved gases to contain the compounds containing CO functional groups (aldehydes, ketones), aromatic and aliphatic hydrocarbons as major pyrolytic products. This low-cost abundant biomass may be used to produce energy and chemicals in a cost-efficient and environmentally friendly way.